PVALB diminishes [Ca2+] and alters mitochondrial features in follicular thyroid carcinoma cells through AKT/GSK3β pathway. Issue 9 (September 2016) - Mendes, Thais Biude; Nozima, Bruno Heidi; Budu, Alexandre; de Souza, Rodrigo Barbosa; Braga Catroxo, Marcia Helena; Delcelo, Rosana; Gazarini, Marcos Leoni; Cerutti, Janete Maria
Abstract : We have identified previously a panel of markers (C1orf24, ITM1 and PVALB) that can help to discriminate benign from malignant thyroid lesions. C1orf24 and ITM1 are specifically helpful for detecting a wide range of thyroid carcinomas, and PVALB is particularly valuable for detecting the benign Hürthle cell adenoma. Although these markers may ultimately help patient care, the current understanding of their biological functions remains largely unknown. In this article, we investigated whether PVALB is critical for the acquisition of Hürthle cell features and explored the molecular mechanism underlying the phenotypic changes. Through ectopic expression of PVALB in thyroid carcinoma cell lines (FTC-133 and WRO), we demonstrated that PVALB sequesters free cytoplasmic Ca 2+, which ultimately lowers calcium levels and precludes endoplasmic reticulum (ER) Ca 2+ refilling. These results were accompanied by induced expression of PERK, an ER stress marker. Additionally, forced expression of PVALB reduces Ca 2+ inflow in the mitochondria, which can in turn cause changes in mitochondria morphology, increase mitochondria number and alter subcellular localization. These findings share striking similarity to those observed in Hürthle cell tumors. Moreover, PVALB inhibits cell growth and induces cell death, most likely through the AKT/GSK-3β. Finally, PVALB expression coincides with Ca 2+ deposits in HCA tissues. Our data support the hypothesis that the loss of PVALB plays a role in the pathogenesis of thyroid tumors.